The risk of cardiometabolic disorders in lean non-alcoholic fatty liver disease: A longitudinal study - Ehimen C. Aneni; Marcio Sommer Bittencourt; Catherine Teng; Miguel Cainzos-Achirica; Chukwuemeka U. Osondu; Ahmed Soliman; Mouaz Al-Mallah; Matthew Buddoff; Edison R. Parise; Raul D. Santos; Khurram Nasir (Elsevier, 2020)
Background: Recent studies suggest that non-alcoholic fatty liver disease (NAFLD) in lean (BMI<25 ​kg/m2) individuals presents a distinct phenotype. We sought to determine the cardiometabolic consequences of lean NAFLD in a population cohort of relatively young asymptomatic individuals who participated in a voluntary routine health promotion evaluation in Brazil. Methods: We analyzed data in our population collected from 2004 to 2016. Medical and demographic history, anthropometric measures, and fasting blood samples were obtained. Participants had ultrasonography to assess for fatty liver. We defined NAFLD as fatty liver in individuals scoring below 8 on the alcohol use disorders identification test (AUDIT). We included data from 9137 individuals who had complete data at baseline and at follow-up. Results: The prevalence of lean NAFLD in our cohort was 3.8%. Over the median follow-up period of 2.4 years (range 0.5-9.9 years), lean individuals had 74% (HR: 1.74 (1.39-2.18)) and 67% (1.67 (1.29-2.15)) greater risk of developing elevated BP and elevated glucose, and nearly 3 times the risk of atherogenic dyslipidemia (HR: 2.98 (2.10-4.24)) compared to lean individuals without NAFLD. Lean NAFLD individuals also had higher risk of developing elevated glucose (HR: 1.37 (1.07-1.75)) and atherogenic dyslipidemia (1.46 (1.05-2.01)) compared to non-lean individuals without NAFLD. However, there was no significant difference in the risk of elevated BP, elevated glucose or atherogenic dyslipidemia between lean NAFLD and non-lean individuals with NAFLD in fully adjusted models. Conclusion: Lean NAFLD is not metabolically benign. Further cardiovascular risk stratification and appropriate preventive measures should be considered in lean individuals who present with NAFLD.